Self-Esteem dengan Perilaku Schadenfreude pada Mahasiswa Universitas di Pulau Jawa - Marsseda, Salsabila Agustine; Soetjiningsih, Christina Hari; Sarajar, Dewita Karema (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2025)
Self-esteem is a crucial factor in an individual's life that influences various psychological and social aspects, including schadenfreude, which refers to the pleasure one feels at another person's misfortune. This study aims to examine the relationship between self-esteem and schadenfreude behavior among university students in Java, Indonesia. This research employs a quantitative approach with a correlational design. The study involved 253 students selected using a purposive sampling technique. Self-esteem was measured using the Rosenberg Self-Esteem Scale (RSES), while schadenfreude behavior was assessed using the Schadenfreude Scale developed by Crysel and Webster (2018). Statistical analysis revealed a significant negative correlation between self-esteem and schadenfreude, with a correlation value of r = -0.699; p < 0.05. The majority of respondents exhibited moderate levels of self-esteem (48.86%) and schadenfreude behavior (51.14%). These findings imply that the higher an individual's self-esteem, the lower their tendency to experience schadenfreude, and vice versa.